Job satisfaction, life satisfaction, and associated factors among hospital nurses: a cross-sectional study in Türkiye - Volkan Medeni; İrem Medeni; Gizem Altunay; Asiye Uğraş Dikmen; Mustafa Necmi İlhan (Scientific Reports)
Abstract Job satisfaction strongly affects nurses’ life satisfaction and is directly affected by life satisfaction. Our study aimed to determine nurses’ life and job satisfaction, show their relationship, and evaluate the factors affecting them. This cross-sectional study was conducted in 2022 at a university hospital in Türkiye. The study population included all nurses working at the hospital for at least one month, and 920 nurses participated. Data were collected using a structured questionnaire, which consisted of sections on sociodemographic characteristics, job and life satisfaction, and factors related to the nursing profession. Job satisfaction was measured using the Index of Job Satisfaction, while life satisfaction was assessed with the Life Satisfaction Scale, both validated tools. Data collection occurred during periodic health examinations through face-to-face interviews. Most participants chose the nursing profession willingly and found it suitable for themselves. However, many reported dissatisfaction with their earnings. Higher job satisfaction was associated with older age, having children, good perceived health, shorter weekly working hours, willingly choosing the nursing profession and unit, and favorable working conditions and income. Similarly, life satisfaction was higher among those with good perceived health, fewer weekly working hours, willingly chosen profession and unit, and no smoking or chronic diseases. Supportive working conditions and adequate income strongly influenced both job and life satisfaction. A significant, positive, and moderate correlation was found between job and life satisfaction, highlighting their interconnectedness. These findings suggest that improving nurses’ working conditions, ensuring adequate income, and supporting healthier lifestyles could enhance job and life satisfaction. Enhancing working conditions is essential to improving nurses’ job satisfaction, which, in turn, positively impacts their overall life satisfaction. Policymakers should prioritize initiatives that address workplace challenges and foster a supportive environment for nurses.